Financial Performance Analysis of Regional Original Income, General Allocation Funds and Special Allocation Funds Based on The Ratio of Independence, Effectiveness, and Efficiency in Districts/Cities The Province of North Sumatra - Fahrum Nisa; Puja Rizqy Ramadhan; Dito Aditia Darma (Yayasan Multidimensi Kreatif, 2024)
This research was conducted for the following purposes: (1) To determine and analyze the financial performance of district/city regional governments in North Sumatra Province. (2) To determine and analyze the impact of the General Allocation Fund on the financial performance of district/city regional governments in North Sumatra Province. (3) To identify and analyze the impact of Special Allocation Funds on the financial performance of district/city governments in North Sumatra. This research uses secondary data in the form of data on the realization of the North Sumatra Province Regency/City APBD for the 2022-2023 period. This research uses descriptive research using analysis of independence ratios, effectiveness ratios, and efficiency ratios and ratios to assess the performance of districts/cities in North Sumatra Province, Sumatra. The results of this research show that, based on the analysis of these three ratios, they can influence the financial performance of district/city governments in North Sumatra.